HUBUNGAN EMPATI DENGAN PERILAKU PROSOSIAL PADA RELAWAN KSR PMI KOTA MEDAN - Istiana Istiana (Jurnal Diversita, 2016)
This study aims to determine the relationship of empathy and prosocial behavior in KSRPMI volunteers Medan. Subjects in this study were volunteers KSR PMI Medan whichnumbered 60 people. Aspects that are used as a measuring tool prosocial behavior, usethe opinion of Baron and Bryne, namely Helping a Stanger Distress, deterring awrongdoer and Resist. Aspects that are used as a measure of empathy, using the Davisopinion, namely Perspective taking, Emphatic Concern, Personal Distress, and Fantasy.Measuring instrument used is a Guttman scale consists of 36 items prosocial behavior(α = 0.936) and a Likert scale consists of 42 items empathy (α = 0.932). Data analysisusing techniques r Product Moment. Based on data analysis, found that the hypothesisproposed in this study received, that there is a relationship between empathy andprosocial behavior in KSR PMI volunteers Medan. This is evidenced by the value orcoefficient of correlation (rxy = 0.328, p> 0.05), as well as empathy influence prosocialbehavior in KSR PMI volunteers in Medan by 10.8%, further views from the calculationof hypothetical mean and the empirical mean and standard deviation is known that thelevel of prosocial behavior and empathy in KSR PMI volunteers Medan is high seen bythe average empirical value is higher than the average value of the hypothetical empathyand prosocial behavior.